2019
DOI: 10.3390/nu11122860
|View full text |Cite
|
Sign up to set email alerts
|

Association of Health Status and Health Behaviors with Weight Satisfaction vs. Body Image Concern: Analysis of 5888 Undergraduates in Egypt, Palestine, and Finland

Abstract: Little is known about the relationships between weight satisfaction, body image concern, healthy nutrition, health awareness, and physical activity among college students across culturally different countries. We assessed country and sex-specific associations between health status (self-rated health, depression, BMI), healthy behavior (healthy nutrition, physical activity, health awareness), weight satisfaction, and body image concern via a cross-sectional survey (5888 undergraduates) in Egypt, Palestine, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 64 publications
5
13
0
Order By: Relevance
“…In addition, despite men having reported more frequent binge drinking and lower consumption of fruits and vegetables, their unhealthy nutrition score was lower compared to that of women. These findings overlap with the results from other studies [26,31,[46][47][48]. However, men more frequently reported excellent/good self-rated health compared to women.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, despite men having reported more frequent binge drinking and lower consumption of fruits and vegetables, their unhealthy nutrition score was lower compared to that of women. These findings overlap with the results from other studies [26,31,[46][47][48]. However, men more frequently reported excellent/good self-rated health compared to women.…”
Section: Discussionsupporting
confidence: 54%
“…In other studies on the health behaviors of physical education students from Gdańsk and Murcia, it was confirmed that there is diversity in certain aspects of lifestyle, with Spanish students showing more rational dietary choices [ 21 ]; this is not unequivocally confirmed in the authors’ research. The authors of research on the relationship between satisfaction with body mass, rational nutrition, health awareness and physical activity of students from various cultures (Egypt, Palestine, and Finland) [ 36 ] also suggested the justification for continuing research in various countries.…”
Section: Discussionmentioning
confidence: 99%
“…The self-administered questionnaire gathered general health data: socio-demographic (sex, age, year of study, living arrangements during university terms); health (self-rated general health, health awareness); lifestyle (IDU, smoking, heavy episodic drinking, problem drinking, possible alcohol dependence); mental wellbeing variables (depressive symptoms, perceived stress), university related educational questions (academic achievement compared to peers), and information on religiosity and financial burdens. The tool was used and field-tested across many student populations [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Variables with several response options were later dichotomized as shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%